Faktor Faktor Penyebab Terjadinya ISPA pada Balita : Systematic Review - Fitrah Hidayahturrahmat M. H; Sulistyawati Sulistyawati; Tri Wahyuni Sukesi (Yayasan Literasi Sains Indonesia, 2026)
Acute Respiratory Tract Infections (ARI) are the leading cause of morbidity and mortality among under-fives in Indonesia. Toddlers have a high risk of developing ARI due to their suboptiomal immune system. Environmental factors such as exposure to cigarette smoke, overcrowding, and lack of exclusive breastfeeding can exacerbate this condition. This study aimed to identify the main factors influencing the incidence of ARI in under-fives through systematic analysis.This study used a systematic literature review method with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. Data wew obtained from Google Scholar using the keywords “risk factors”, “ARI”, and “under-five” for period 2019-2024. From the initial 8.200 articles, a selection process was carried out until 10 relevant articles were selected for further analysis.Exposure to indoor tobacco smoke worsens air quality and increases the risk of respiratory infections. Overcrowding and inadequate ventilation degrade air quality, creating ideal conditions for infection transmission. Exclusive breastfeeding, which is rich in immunoglobulin, has been shown to provide important protection against ARI. Therefore, prevention efforts should focus on reducing exposure to tobacco smoke, improving living conditions, and increasing education on the importance of exclusive breastfeeding.The main factors influencing the incidence of ARI in children under-five are exposue to tobacco smoke, overcrowding, and lack of exclusive breastfeeding. ARI prevemtion efforts should include interventions against these factors to reduce the preva;ence and impact on under-fives